Strategies to enhance the effects of pictorial warnings for cigarettes: results from a discrete choice experiment - Thrasher, James F.; Islam, Farahnaz; Arillo‐Santillán, Edna; Rodriguez‐Bolaños, Rosibel; Saenz de Miera Juarez, Belen; Hardin, James W.; Barrientos‐Gutierrez, Inti (Addiction (Abingdon, England), 2022)
Aims To measure the effects of changing attributes of pictorial health warning labels (HWLs) on cigarette packs in a country that has already implemented pictorial HWLs. Measures For each choice set, participants were presented with two cigarette packs and asked the following three questions: (1) ‘If only these two cigarette packs were available, which would you buy?’; (2) ‘Each of these two packs has warnings on the front and back about the health effects of smoking. Which of these warnings best informs you about the dangers from smoking?’; and (3) ‘Which warning most makes you think about quitting smoking?’. As recommended for best practices in discrete choice experiments, each of these questions was followed by an ‘opt‐out’ question for participants to indicate whether they really believed there was a difference between the options presented (i.e. ‘Would you really choose one of them?’; ‘Do you really think that either of these warnings informs you about dangers from smoking?’; or ‘Do you really think that either of these warnings would make you think about quitting smoking?’, respectively). Each choice set could be viewed for as long as the participant wished. For each choice question (i.e. willingness to buy, informative, motivating to quit), the pack chosen was coded as 1 and the other pack as 0, with both packs being given a value of 0 if the participant ‘opted out’. Design A within‐subject discrete choice experiment that involved systematic manipulation of pictorial HWL size [75 versus 30% (current policy)]; inclusion of imagery on the back of the pack [versus none (current policy)]; and color formatting [black on yellow versus yellow on black (current policy)]. Setting Mexico, on‐line panel. Participants Adult smokers (n = 705). Measurements For each choice set, participants selected one pack as having the most informative HWL about smoking harms, the one that makes them think the most about quitting and the one they were most willing to buy. We assessed the independent and interactive effects of HWL attributes on choices. Findings Larger HWL size on the pack front (75 versus 30%) and inclusion of a pictorial image on the pack back were both independently associated with lower willingness to buy a pack [b = −0.228, standard error (SE) = 0.023 and −0.089, SE = 0.016, respectively] and greater perception of an HWL as informative (b = 0.214, SE = 0.022, and 0.191, SE = 0.017, respectively) and motivating to quit (b = 0.251, SE = 0.023 and 0.194, SE = 0.017, respectively). HWL with black text and yellow background were perceived as less informative (b = −0.037, SE = 0.016) and less motivating to quit (b = −0.032, SE = 0.015) compared with yellow text on a black background. Conclusions Among adult Mexican smokers, pictorial health warning labels on cigarette packages that are larger or cover both sides of the pack appear more effective at lowering purchase intentions and increasing risk perceptions and motivation to quit than smaller health warning labels or health warning labels with imagery only on the pack front.